Improving Access to Historic Buildings: Some English Experience - Walter, Nigel (Protection of Cultural Heritage, 2022)
In England, accessibility to historic buildings falls under the Equality Act 2010, for which a key concept is the making of ‘reasonable adjustments’ to physical features of a building; this acknowledges that a blanket application of technical requirements would be detrimental to some historic buildings, and that equal access may not be achievable in every case. This paper approaches accessibility in historic buildings in England from two angles. The first is a consideration of two separate guidance documents, from Historic England and from the Church of England respectively; each document is outlined, offering points of comparison with guidance in other jurisdictions. One consistent theme in these documents is the positive framing of accessibility as of benefit not only for those with disabilities, but also for all users and potentially for the heritage itself. The second aspect of the paper comprises three case study projects from my own practice, spread across a range of building types, ages, and grades of protection, which together demonstrate by example some of what is currently considered possible in England, and illustrate how practice relates to policy and guidance. The paper ends by briefly reflecting on what light accessibility policy might shed on some broader questions of heritage concern.